RHIZOSPHERE pH AND PHOSPHATASE ACTIVITY IN ORTHIC ALLOPHANIC SOIL UNDER Pinus radiata SEEDLINGS GROWN WITH BROOM AND RYEGRASS - Rivaie, Achmad A.; Tillman, Russ W. (Secretariat of Forestry Research and Development Agency, 2009)
Under Pinus radiata plantations where the tree spacing is wider and most soils are phosphorus (P) deficient, the radiata tree response to P fertilizer is expected to be more influenced by the interaction between the applied P fertilizer, the tree and understorey vegetation. Therefore, a better understanding of the soil P chemistry under radiata pine trees in association with other plants is required. We investigated the effect of broom (Cytisus scoparius L.) and ryegrass (Lolium multiflorum) grown with radiata seedlings in Orthic Allophanic Soil treated with 0, 50, and 100 μg P g-1 soil of TSP on the pH and phosphatase activity in the rhizosphere soils under glasshouse condition. The pHs of radiata rhizosphere soils either grown with broom or grass were lower than those in the bulk soils and the bulk and rhizosphere soils of grass and broom, whether they were grown alone or grown with radiata at the applications of 50 and 100 μg P g-1 soil. These results suggest that P application enhanced root induced acidification in a P-deficient Allophanic Soil under radiata. The soils in the rhizosphere of grass and broom, grown in association with radiata, were also acidified by the effect of radiata roots. Acid phosphatase activity in soils under radiata, grass and broom decreased with an increased rate of P application. At all P rates, acid phosphatase activity was higher in the rhizosphere of radiata grown with broom than in the bulk soils. The phosphatase activity in the rhizosphere soil of radiata grown with broom was also higher than that of radiata grown with grass, but it was slightly lower than that in the rhizosphere of broom grown alone. These results suggest that broom may have also contributed to the higher phosphatase activity in the rhizosphere soils than in the bulk soils of broom and radiata when they were grown together